The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1103/physreve.71.046109
|View full text |Cite
|
Sign up to set email alerts
|

Blocking temperature in magnetic nanoclusters

Abstract: A recent study of nonextensive phase transitions in nuclei and nuclear clusters needs a probability model compatible with the appropriate Hamiltonian. For magnetic molecules a representation of the evolution by a Markov process achieves the required probability model that is used to study the probability density function (PDF) of the order parameter, i.e. the magnetization. The existence of one or more modes in this PDF is an indication for the superparamagnetic transition of the cluster. This allows us to det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…For he spin model we will consider two cases, firstly we consider a system consisting of a single large spin, typically used in connection with nano-magnets, and indicated by LS. Secondly we will consider the many spin system, typically used to calculate the blocking temperature [3] or other phase-transitions [9,10,11,12], and indicated by MS. For the M/M/∞-queue we will use the maximum entropy principle to show that it is able to distinguish between different initial conditions. Furthermore we will calculate the Shannon entropy of the queue and of the "quantum" model equivalent to the queue and show that the entropies have completely different behavior with respect to β .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For he spin model we will consider two cases, firstly we consider a system consisting of a single large spin, typically used in connection with nano-magnets, and indicated by LS. Secondly we will consider the many spin system, typically used to calculate the blocking temperature [3] or other phase-transitions [9,10,11,12], and indicated by MS. For the M/M/∞-queue we will use the maximum entropy principle to show that it is able to distinguish between different initial conditions. Furthermore we will calculate the Shannon entropy of the queue and of the "quantum" model equivalent to the queue and show that the entropies have completely different behavior with respect to β .…”
Section: Resultsmentioning
confidence: 99%
“…In ref. [3], we compared the PDF of magnetization based on the assignment (1) with the PDF based on the Markov representation and we found that they are different. In order to indicate the possible origin of this difference we briefly indicate the steps necessary to achieve the Markov representation.…”
Section: The Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Since S > 1/2 there is an underscreened Kondo effect, the development of which is hampered by the anisotropy as has been shown by timedependent numerical renormalization group. 17 As the quantum character of the macrospin is not accounted for by simple Langevin dynamics, 7 different approaches [18][19][20] have been suggested to treat the macro-or many-spin dynamics in contact with bosonic baths by means of quantum master-equation approaches and to determine, e.g., the blocking temperature. The importance of a manyspin model, for example, is demonstrated by studies of the probability density function of the macrospin obtained by replacing thermal with Markov processes.…”
Section: Introductionmentioning
confidence: 99%